Brachial Artery Aneurysm in a 7-Month-Old Infant: Case Report and Literature Review. Issue 2 (February 2016) - Gangopadhyay, Noopur; Chong, Tae; Chhabra, Avneesh; Sammer, Douglas M.
Abstract : Summary: Congenital upper extremity aneurysms are very rare and can be challenging to diagnose and treat. Although they can present as an isolated finding, they are often associated with other systemic conditions. We present a rare case of brachial artery aneurysm in a 7-month-old boy. The patient was evaluated with ultrasound, magnetic resonance angiography, and vein mapping before surgical reconstruction. After excision of the aneurysm, the brachial artery was reconstructed with an interposition saphenous vein graft. Because of potentially associated diagnoses and the possibility of concurrent aneurysms, this condition requires multidisciplinary management.